2019
DOI: 10.1038/s41598-019-42807-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic and experimental study on thermal conductivity of bulk and porous cerium dioxide

Abstract: Cerium dioxide (CeO 2 ) is a surrogate material for traditional nuclear fuels and an essential material for a wide variety of industrial applications both in its bulk and nanometer length scale. Despite this fact, the underlying physics of thermal conductivity ( k L ), a crucial design parameter in industrial applications, has not received enough attention. In this article, a systematic investigation of the phonon transport properties was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
5
13
0
Order By: Relevance
“…Additionally, phonon lifetime measurements using neutron scattering supplemented by first principles calculations in UO 2 suggested that optical modes also contribute to thermal transport in materials with the fluorite crystalline structure . Recent atomic level conductivity calculations have confirmed similar behavior in CeO 2 . More accurate analysis using actual phonon dispersion will require reformulation of the phonon‐defect scattering rates for each phonon mode, but will not significantly change the conclusion of this work …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Additionally, phonon lifetime measurements using neutron scattering supplemented by first principles calculations in UO 2 suggested that optical modes also contribute to thermal transport in materials with the fluorite crystalline structure . Recent atomic level conductivity calculations have confirmed similar behavior in CeO 2 . More accurate analysis using actual phonon dispersion will require reformulation of the phonon‐defect scattering rates for each phonon mode, but will not significantly change the conclusion of this work …”
Section: Discussionmentioning
confidence: 88%
“…The dislocation line model, which only includes the contribution from the extended strain field, is given byτline-1ω=0.06γ2b2Ndω,where γ ‐Gruneisen parameter, b ‐dislocation line Burgers vector, and N d ‐dislocation line density, defined as the number of lines per unit area, Nd=2πRdnd. Here, we use γ = 2.05 obtained from atomistic calculation of thermal conductivity in CeO 2 . While the scattering from platelet inclusion is:τplate-1ω=24πb2Rd2ndvsω2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ZrS2 ML system, the three-phonon SPS at 300 K increases upon increasing the phonon frequency (above 160 cm -1 as shown in Fig. S2, Supplemental Material [68]), which correspond to the subsequently lower 𝜅 9 [71,72] thereby increasing the scattering channels. The three phonon SPS values for absorption processes at 300 K reach to its minimum at higher frequencies (Fig.…”
Section: E Lattice Thermal Conductivitymentioning
confidence: 99%